Prediction of Bronchopulmonary Dysplasia in Preterm Infants Using Postnatal Risk Factors - Ding, Li; Wang, Huawei; Geng, Haifeng; Cui, Ningxun; Huang, Fengxia; Zhu, Xueping; Zhu, Xiaoli (Frontiers in Pediatrics, 2020)
Objective: To identify postnatal risk factors that predict the occurrence of bronchopulmonary dysplasia (BPD) in preterm infants with gestational age less than or equal to 32 weeks. Methods: A prospective longitudinal study was conducted in 72 preterm infants (30 with BPD and 42 non-BPD controls) admitted to the neonatal intensive care unit (NICU) of the Children’s Hospital of Soochow University during 2017. Basic clinical data from the mothers and postnatal risk factors in the infants, including a neonatal critical illness score (NCIS), were obtained from the clinical records. Soluble B7-H3 (sB7-H3) and interleukin-18 (IL-18) were measured in the serum of the infants at ages 1, 3, 7, 14, and 28 days by ELISA. An early prediction model for BPD was established based on clinical data along with sB7-H3 and IL-18 levels and NCIS using a multiple logistic regression analysis. Results: Electrolyte disturbances, hemodynamically significant patent ductus arteriosus (hs-PDA), and decreased enteral nutrition intake (measured as reaching goal energy intake [120 kcal/kg.d] by enteral feeding after an age of at least 40 days) were found to be correlated to the occurrence of BPD. Serum sB7-H3, IL-18, and NCIS were significantly higher in the BPD group compared to the non-BPD group (p0.05). BPD group had significantly lower enteral fluid and calorie intake compared to the non-BPD group at ages 1, 7, 14, and 28 days. The prediction model, constructed using multiple logistic regression and a combination of sB7-H3 (day 7), IL-18 (day 14), NCIS, and clinical risk factors, had an area under the curve (AUC) of 0.960, with a 86.70% sensitivity and 97.60% specificity. Conclusion: The occurrence of BPD is affected by a combination of multiple postnatal risk factors and a prediction model constructed using a combination of sB7-H3 (7 days), IL-18 (14 days), NCIS, and clinical risk factors (electrolyte disturbances, hs-PDA, and reaching goal energy intake by enteral feeding after an age of at least 40 days) can predict the occurrence of BPD but not the severity of the disease.